2004
DOI: 10.1111/j.1365-2230.2004.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary leukotriene E4 correlates with severity of atopic dermatitis in children

Abstract: Leukotriene E4 (LTE(4)) is elevated in adults with atopic dermatitis (AD). We evaluated whether urinary LTE(4) as a noninvasive marker correlates with clinical indices of disease activity in children with AD. AD patients aged 18 years or younger were eligible for inclusion in the study. Disease severity over the preceding 3 days was evaluated by the SCORing Atopic Dermatitis (SCORAD) index. Severity of AD over the past 12 months was evaluated by the Nottingham Eczema Severity Score (NESS) in Chinese. Urinary L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Four boys and three girls, with a median (range) age of 12 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years, participated in the study. Their median (range) SCORAD scores before and after treatment were 34.7 (16.5-54.8) and 17.0 (6.9-36.9) (Figure 1; pv0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four boys and three girls, with a median (range) age of 12 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years, participated in the study. Their median (range) SCORAD scores before and after treatment were 34.7 (16.5-54.8) and 17.0 (6.9-36.9) (Figure 1; pv0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The elevated urinary concentration of LTE 4 , a stable metabolite of LTC 4 and LTD 4 , and being a useful index of whole-body cysteinyl LT production in vivo [11], have been reported in patients with AD [12][13][14]. In a recent study of 126 children with AD [15], we also found significant correlations between the urinary LTE 4 concentration and overall SCORAD score (r50.270, p50.002), its extent (r50.185, p50.038) and intensity components (r50.247, p50.005). These evidences supported a potential role for increased LT production in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This was a self-administered questionnaire and the validated Chinese version was provided [14]. In the modified Chinese version, the surface diagram is enlarged for enhanced clarity and patients are requested to put a 'tick' in boxes of body-parts currently affected with eczema [11,14,15]. The total NESS score further categorized AD severity into three groups: mild, moderate or severity.…”
Section: Study Populationmentioning
confidence: 99%
“…It measures the extent, intensity, pruritus, and sleep loss related to AD over the preceding 3 days 3,4 . The severity of AD has also been found to be associated with the levels of various chemokines 5–7 . These chemokine markers have been extensively studied in both adults and children.…”
Section: Introductionmentioning
confidence: 99%